1970
DOI: 10.3126/jncs.v25i0.3312
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Alloying Elements on the Corrosion Behavior of Amorphous W–Zr–(15–33)Cr Alloys in 1 M NaOH Solution

Abstract: Roles of alloy-constituting elements on the corrosion behavior of the sputter-deposited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The immunity to passivity breakdown like the pitting corrosion is one of the most interesting characteristics of the zirconium containing alloys. It has been reported that the synergistic improvement in the resistance to the passivity breakdown of the alloys in chloride-containing aggressive environments was reported when simultaneous additions of tungsten, zirconium, chromium or nickel to the sputter-deposited ternary W-xZr-yCr Bhattarai 2010, 2011;Kumal and Bhattarai 2010; Bhattarai b, 2011 Bhattarai b, 2011 or W-xCr-yNi (Bhattarai 2009; Bhattarai and Kharel 2009−10;Kharel and Bhattarai 2009; Bhattarai 2010 a) alloys instead of single addition of zirconium, chromium or nickel metals. The synergistic improvement in the resistance to corrosion as well as the pitting corrosion of these sputter-deposited binary and ternary tungsten-based alloys was attributed to the formation of double oxyhydroxide passive films of the alloy-constituting elements from the XPS analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The immunity to passivity breakdown like the pitting corrosion is one of the most interesting characteristics of the zirconium containing alloys. It has been reported that the synergistic improvement in the resistance to the passivity breakdown of the alloys in chloride-containing aggressive environments was reported when simultaneous additions of tungsten, zirconium, chromium or nickel to the sputter-deposited ternary W-xZr-yCr Bhattarai 2010, 2011;Kumal and Bhattarai 2010; Bhattarai b, 2011 Bhattarai b, 2011 or W-xCr-yNi (Bhattarai 2009; Bhattarai and Kharel 2009−10;Kharel and Bhattarai 2009; Bhattarai 2010 a) alloys instead of single addition of zirconium, chromium or nickel metals. The synergistic improvement in the resistance to corrosion as well as the pitting corrosion of these sputter-deposited binary and ternary tungsten-based alloys was attributed to the formation of double oxyhydroxide passive films of the alloy-constituting elements from the XPS analyses.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the sputter-deposited amorphous or/and nanocrystalline ternary W-xCr-yNi (Bhattarai, 2009(Bhattarai, , 2010bBhattarai and Kharel, 2009-10;Kharel and Bhattarai, 2009) and W-xZr-yCr (Aryal and Bhattarai, 2010cBhattarai, , 2011aBhattarai, , 2011bBhattarai and Aryal, 2011;Kumal and Bhattarai, 2010) alloys were spontaneously passivated showing significantly higher corrosion resistance than those of alloy-constituting elements in different aggressive solutions. In this context, the present work is focused to study the effects of the eco-friendly green corrosion inhibitor of sodium nitrite to control the corrosion of two sputterdeposited W-42Cr-5Ni and Cr-10Zr-10W alloys in 0.5 M NaCl and 1 M NaOH solutions open to air at 25ºC using corrosion tests and mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the sputter-deposited amorphous/nanocrystalline W-xZr-yCr [31][32][33][34][35][36][37] and W-xCr-yNi [31,[38][39][40][41] alloys were spontaneously passivated showing higher corrosion resistance properties than those of their alloy-constituting elements in different aggressive acidic to alkaline solutions. In this context, the present work is focused to study the effects of the eco-friendly green corrosion inhibitor of sodium nitrite on the corrosion behavior and inhibition mechanism of two sputterdeposited W-80Cr-10Zr and W-42Cr-5Ni alloys in 0.5 M NaCl solution, open to air at 25ºC using corrosion tests and open circuit potential measurement.…”
Section: Introductionmentioning
confidence: 99%